2023
DOI: 10.3390/nu15132969
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin D Intake in Italian Subjects: Validation of a Frequency Food Questionnaire (FFQ)

Abstract: Vitamin D plays a crucial role in calcium and phosphate metabolism, relating to bone health and preventing metabolic bone disorders such as rickets and osteomalacia. Vitamin D deficiency (serum 25-OH-D values <20 ng/mL or 50 nmol/L) is common also in Italian people; it is recommended to maintain levels above 30 ng/mL (75 nmol/L) in categories at risk. Supplementation and/or fortification with either ergocalciferol (vitamin D2) or cholecalciferol (vitamin D3) aimed to modify this condition have commonly been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
2
2
Order By: Relevance
“…that are rich in Vit D but also rich in cholesterol, one of the major modifiable cardiovascular risk factors [18]. However, the results of this study are not similar to those of other authors who found either that there was no significant difference in dietary Vit D intake between different age groups [19], or that Vit D intake increased with age [20]. Nevertheless, in these studies, there was a significant increase in Vit D deficiency with age in the populations studied, which suggests that the increase in Vit D intake with age in these study populations was measures to compensate for Vit D deficiency in older subjects, especially as these regions are less sunny.…”
Section: Discussioncontrasting
confidence: 99%
“…that are rich in Vit D but also rich in cholesterol, one of the major modifiable cardiovascular risk factors [18]. However, the results of this study are not similar to those of other authors who found either that there was no significant difference in dietary Vit D intake between different age groups [19], or that Vit D intake increased with age [20]. Nevertheless, in these studies, there was a significant increase in Vit D deficiency with age in the populations studied, which suggests that the increase in Vit D intake with age in these study populations was measures to compensate for Vit D deficiency in older subjects, especially as these regions are less sunny.…”
Section: Discussioncontrasting
confidence: 99%
“…The difference in the prevalence of AFF could be accounted for by different baseline risk factors between ethnic groups and other risk factors such as a higher prevalence of vitamin D deficiency in the Lebanese population. 11 , 12 The prevalence in our population was found to be much lower than the prevalence of AFFs seen in the Australian (5%) population. 13 However, it is similar to that seen in one South Korean study (1.2%), an unexpected finding considering that Asian populations are at higher risk for AFFs.…”
Section: Discussioncontrasting
confidence: 68%
“…The intakes of calcidiol (25(OH)D3; 0.0321 vs. 0.0333 mg/day; p-value = 0.690) and cholecalciferol (also known as vitamin D3; 0.8677 vs. 0.7698 mg/day; p-value = 0.684) were very similar and higher in male counterparts, respectively, although without statistical differences, which could be explained by the differences in the intakes of eggs and meat explained previously [2,14], although further analysis would be needed.…”
Section: Resultsmentioning
confidence: 71%